ANALISIS KESESUAIAN PENGATURAN BADAN USAHA MILIK DESA DENGAN NILAI-NILAI PANCASILA - Gani Wardana, Allan Fatchan (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
Villages as legal entities have more authority to regulate and manage their territorial affairs autonomously, one of which is to form Village-Owned Enterprises (BUM Desa). BUMDesa is one of the important capitals for the village to realize community empowerment and must be managed with a spirit of kinship and mutual cooperation . The regulations regarding BUMdesa are scattered in various regulations. This research examines two things, first how BUMDesa is regulated in statutory regulations, second is whether the regulation regarding BUMDesa is in accordance with Pancasila values. This study uses a normative juridical method with a statutory approach. The results of the study concluded thatVillage BUM regulations are regulated in 3 (three) levels of statutory regulations (Laws, Government Regulations, and Ministerial Regulations). A very comprehensive arrangement is even regulated at the level of a Ministerial Regulation. Village BUM are pillars and milestones that can encourage village progress so that important things should be regulated at the level of Law, Second, Village BUM regulations in various regulations are normatively in accordance with Pancasila values, namely humanitarian, unity, populist principles. and justice has been used as the basis for the establishment, management, development, and utilization of the Village-Owned Enterprise (BUM Desa) business results.